2020
DOI: 10.1038/s41430-020-0689-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of dietary acid load with serum bicarbonate in chronic kidney disease (CKD) patients

Abstract: Association of dietary acid load with serum bicarbonate in chronic kidney disease (CKD) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In other study (27), mean value of NEAP of CKD patients was 50.1±13.1mEq/day. In Brazilian study (28), the median value of PRAL was 6.8 mEq/day and of NEAP was 53.1 mEq/day for CKD patients. In African American CKD patient (15),Median estimated NEAP was estimated 71 mEq/d.Another study (29) showed that median value of estimated DAL, is 47.24 mEq/d .The study among Venezuelan CKD children (30) indicated that mean of PRAL is 16 ± 10.7 mEq/day.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In other study (27), mean value of NEAP of CKD patients was 50.1±13.1mEq/day. In Brazilian study (28), the median value of PRAL was 6.8 mEq/day and of NEAP was 53.1 mEq/day for CKD patients. In African American CKD patient (15),Median estimated NEAP was estimated 71 mEq/d.Another study (29) showed that median value of estimated DAL, is 47.24 mEq/d .The study among Venezuelan CKD children (30) indicated that mean of PRAL is 16 ± 10.7 mEq/day.…”
Section: Discussionmentioning
confidence: 84%
“…Because, while the validity ofdietary acidi load values calculated by PRAL formula versus it's measured vale from urine has been con rmed (47,48), due to the limited interpretation of the results obtained from the formulas for estimating the dietary acid load in different situations of urinary pH and blood bicarbonate concentration (28), long-term study with more and more population and taking into account blood bicarbonate concentration and urinary pH is proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The PRAL and NEAP scores have been validated and are frequently utilized in epidemiological research, displaying a strong association with acid load as measured in 24 h urine [8,11]. Finally, the CHNS did not collect data reflecting low-grade organic metabolic acidosis, such as serum pH, urine pH, or bicarbonate concentration, but some studies conducted in healthy and CKD populations have shown that DAL correlates well with endogenous acid-base status [14,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Western diets typically consist of large amounts of animal protein and processed foods, which produce a high dietary acid load (DAL). In comparison, vegetarian/vegan diets with high fruit and vegetable content are often low in acid load and high in potassium bases, which can result in a net alkali load [ 8 , 61 ]. In recent years, the impact of DAL on health and disease has gained increasing recognition [ 20 , 113 , 143 , 154 ].…”
Section: Introductionmentioning
confidence: 99%